PERANCANGAN DATABASE ROTI BAKAR SELERA DENGAN MICROSOFT ACCESSDESIGNING A ROTI BAKAR SELERA DATABASE WITH MICROSOFT ACCESS - Alya Zahra Firdaus; Septi Widyastuti; Syarofi Sayiddiya Ulhaq; M. Irzsa Zeqty Gustian; Derry Dardanella (SUAN PUBLISHER, 2025)
The rapid advancement of information technology, particularly Microsoft Access, presents a significant opportunity for Micro, Small, and Medium Enterprises (MSMEs) to enhance their financial and income data management. Despite these advancements, a notable number of MSMEs, including